Existence and Stability of Periodic Solution to Delayed Nonlinear Differential Equations. (13th April 2014) - Gu, Xiang; Wang, Huicheng; Wong, P. J. Y.; Xia, Yonghui
Abstract : The main purpose of this paper is to study the periodicity and global asymptotic stability of a generalized Lotka-Volterra's competition system with delays. Some sufficient conditions are established for the existence and stability of periodic solution of such nonlinear differential equations. The approaches are based on Mawhin's coincidence degree theory, matrix spectral theory, and Lyapunov functional.